A Patched-Like Protein PsPTL Is Not Essential for the Growth and Response to Various Stresses in Phytophthora sojae - Xue, Zhaolin; Wang, Weizhen; Shen, Jinghuan; Zhang, Jinhui; Zhang, Xitao; Liu, Xili (Frontiers in Microbiology, 2021)
Patched (Ptc) and Patched-related (PTR) proteins containing sterol-sensing domain (SSD) and patched domain are highly conserved in eukaryotes for lipid transport and metabolism. Four proteins containing predicted SSD and Patched domains were simultaneously found by searching the Phytophthora sojae genome database, and one of them was identified as a Patched-like (PTL) protein. Here, we investigated the biological function of PsPTL. The expression level of PsPTL was higher during mycelial and sporulation stages, compared to zoospore, cyst, and germinated-cyst stages, without significant change during infection. However, deletion of PsPTL using CRISPR/Cas9 had no significant effect on the growth, development, or virulence of P. sojae. Further investigations showed that PsPTL is not important for P. sojae to cope with external stresses such as temperature, pH, oxidative and osmotic pressure. In addition, this gene did not appear to play an essential role in P. sojae’s response to exogenous sterols. The transcript levels of the other three proteins containing predicted SSD and Patched domains were also not significantly upregulated in PsPTL knockout transformants. Our studies demonstrated that PsPTL is not an essential protein for P. sojae under the tested conditions, and more in-depth research is required for revealing the potential functions of PsPTL under special conditions or in other signaling pathways.